CLINICOPATHOLOGICAL SPECTRUM OF UROTHELIAL CARCINOMA OF THE URINARY BLADDER – A STUDY OF 541 CASES AT AFIP PAKISTAN: Multi-Tier Medical Support - Ahmed, Rabia; Hashmi, Shoaib Naiyar; Din, Hafeez Ud; Muhammad, Iqbal (Pakistan Armed Forces Medical Journal, 2015)
Objective: To analyze the clinicopathological spectrum of urothelial carcinoma of urinary bladder.Study Design: Descriptive case series.Place and Duration of Study: Armed Forces Institute of Pathology (AFIP), from 1st January 2012 to 31st October 2013.Patients and methods: All cases of urothelial carcinoma were retrieved from AFIP tumour registry. Age, gender, histological type, grade and variant of tumour was noted. The data was analyzed by using computer software program SPSS version 19. Descriptive statistics and frequencies were calculated for age, gender, histological type, grade and variants.Results: A total of 541 cases of urothelial carcinoma were included in the study. The age at presentation ranged from 22 to 94 years with median age of 63.56 ± 12 years. A number (61%) of the cases were from 6th to 8th decade of life. The gender distribution showed 92.8% of patients (n=502) were males and 7.2 % (n=39) were females with male to female ratio of 12.9: 1. The most common histological type was papillary urothelial carcinoma; present in 493 cases (91.1%) followed by nonpapillary urothelial carcinoma; 48 cases (8.9%). Among papillary urothelial carcinomas, 302 cases (61.3%) were high grade and 191 cases (38.7%) were low grade. Among nonpapillary urothelial carcinomas, all were high grade and variant histology was observed in all cases. The variants included squamoid differentiation which was present in 27 cases (56.3%), nested variant in 8 cases (16.7%). The sarcomatoid, undifferentiated and clear cell variants in 3 cases (6.3%) each, micropapillary variant in 2 cases (4.2%), lymphoepithelial-like and plasmacytoid variant in 1 case (2.1%) each.Conclusion: Urothelial carcinoma is more common in males. Most of the tumours are papillary urothelial carcinomas. Most of them are high grade and pure urothelial carcinomas. A number of histologic variants are also recognized. Among them, squamoid differentiation is the most common variant histology.